Control law synthesis of the wind-driven power-plant with variable geometry - Kostjukov, V.A.; Medvedev, M.Y.; Poluyanovich, N.K.; Dubyago, M.N.; Bulanovich, D.I.; Pavlenko, D.D. (EAI Endorsed Transactions on Energy Web, 2019)
The analysis and synthesis of aerodynamic properties of the wind-driven power-plant (WP) construction with a vertical axis of rotation and useful interference of the stator and the rotor, that exceeds classical type analogues on energy characteristics, were conducted. The required functional dependence of the rotor rotative moment of WP on the angular speed of its rotation and the wind speed on the basis of aerodynamic optimization and researches of optimal shape and construction of WP was obtained. Respective aerodynamic power was calculated. The example of frequency stabilization of the rotor rotation through control of variable element of optimized form WP construction was considered. Method of maintaining the given angular speed of the rotor with a given deviation for a given time was proposed.
Keywords: aerodynamic optimization; wind-driven power-plant; synthesis; energy characteristic; interference